A Half-Century of Heterotopic Heart Transplantation in Mice: The Spearhead of Immunology Research - Yin, Decheng; Dewald, Oliver; Peng, Xiangyu; Nie, Wenlong; Rong, Song; Dudziak, Diana; Lehmann, Christian; Hörning, André; Fu, Jian (Transplantology, 2024)
Since the success of solid organ transplants, such as human kidneys, livers and hearts, from the 50s to the 60s in the last century, the field of organ transplantation has progressed rapidly. Mainly due to modifications in surgical operation techniques and improvements in immunosuppressive therapy regimes, organ survival time can now be greatly prolonged. This progress has also been dependent upon the availability of appropriate animal models for organ transplantation. Therefore, the mouse heart transplantation model has developed into an irreplaceable research model for solid organ transplantation, providing indelible contributions to the field. In this review, we will provide an overview of the technical developments in murine heart transplantation, as well as its historical and current role for alloimmune research. Further, we will describe its current fields of application and its scientific achievements before we discuss potential future applications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: heterotopic heart transplantation; immunology; murine transplantation

A Modified Surgical Technique for Kidney Transplantation in Mice - Yin, Decheng; Fu, Jian; Chen, Rongjun; Shushakova, Nelli; Allabauer, Ida; Wei, Xinyi; Schiffer, Mario; Dudziak, Diana; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2022)
Kidney transplantation in mice is a complicated and challenging surgery procedure. There are very few publications demonstrating the key steps of this operation. Therefore, this article introduces the technique and points out the surgical caveats associated with this operation. In addition, important modifications in comparison to the conventional procedure are demonstrated. Firstly, a patch of the abdominal aorta is cut and prepared so that the proximal bifurcations of the renal artery, including the ureteral artery are transected together with the donor kidney en bloc. This reduces the risk of a ureter necrosis and avoids the development of a urinary tract occlusion. Secondly, a new method of the vascular anastomosis is demonstrated that allows the operator to flexibly increase or decrease the size of the anastomosis after renal transplant reperfusion has already been initiated. This avoids the development of vessel strictures and intraabdominal bleeding. Thirdly, a technique that enables the anastomosis of the delicate donor ureter and the recipient bladder that does not cause a trauma is shown. Adopting this protocol can shorten the operation time and reduces the damage to the recipient's bladder, thereby significantly increasing the operation success rate for the recipient mice.
CRIS-Team Scopus Importer:2022-08-19

Blood circuit reconstruction in an abdominal mouse heart transplantation model - Yin, Decheng; Fu, Jian; Allabauer, Ida; Witzke, Oliver; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2021)
The surgical technique of heterotopic abdominal heart transplantation in mice is a standard model for research in transplantation immunology. Here, the established technique for a modified blood circuit reconstruction in a heterotopic abdominal heart transplantation model is presented. This method uses the intrathoracic inferior vena cava (IIVC) instead of the pulmonary artery of the donor heart for the anastomosis to the inferior vena cava of the recipient. It is facilitating and improving success rates for abdominal heart transplantation in mice.
CRIS-Team Scopus Importer:2021-07-02

Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, André (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19